Identifikasi Fungi Endofit dari Rimpang Lengkuas (Alpinia galanga L.) sebagai Antifungi terhadap Candida albicans - Raningsih, Ni Made; Sandy, Putu Wahyu Sri Juniantari (Metamorfosa: Journal of Biological Sciences; Vol 5 No 2 (2018), 2018)
The main objectives of this research were to isolat and identify endophytic fungi antagonists of Candida albicnas from galanga rhizomes. Samples of galanga rhizome were collected from Gitgit plantation in Gitgit village, Buleleng regency. Isolation and identification were conducted in Food Microbiology Laboratory, Faculty of Agriculture, Udayana University. There were three isolates identified with inhibitory persentage againts Candida albicans i.e. Trichoderma viridae (26.07±3.76%) , Trichoderma harzianum (45.11±5.84%) and Fusarium oxyforum (20.11±5.61%).